HUBUNGAN RASA PERCAYA DIRI, PERHATIAN GURU, DAN DUKUNGAN TEMAN SEBAYA DENGAN KEAKTIFAN BELAJAR SISWA DI KELAS - Monica Prima Pramesty; Ignatius Bondan Suratno (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
The purpose of this research was to determine the correlation between: 1) self- confidence and students’ learning activeness in class; 2) teacher’s attention and student learning activeness in class; and 3) peer students support with student learning activeness in class. This type of research was correlational research. The population in this research were 186 students of grade XI SMK Negeri 1 Yogyakarta. The research samples were 93 students taken by a convenience sampling. The data were collected by questionnaires and analyzed by descriptive analysis and Spearman’s Rank correlation. The results of this study indicated that: 1) there was a positive and significant correlation between self-confidence and students’ learning activeness in class (r_count = 0.653 r_table = 0.2309; Sig. (1-tailed) = 0.000); 2) there was no positive and significant correlation between teacher’s attention and student learning activities in class (r_count = 0.003 r_table = 0.2309; Sig. (1-tailed) = 0.490); and 3) there was a positive and significant relationship between peer students support and student learning activeness in class (r_count = 0.428 r_table = 0.2309; Sig. (1-tailed) = 0,000).Keywords: Self-Confidence, Teacher’s Attention, and Peer Students Support.